ANALISIS MELODI VOKAL DAN MAKNA SYAIR MUSIK IRINGAN TARI RADDAT APE NANG DITUMBOK DI DESA TRIMANDAYAN KECAMATAN TELUK KERAMAT KABUPATEN SAMBAS - Nasir Nasir; Nurmila Sari Djau; Christianly Yeri Silaban (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study is backgrounded by the lack of interest of the younger generation towards the traditional art Raddat Ape Nang Ditumbok as a heritage in Trimandayan Village, Teluk Keramat District, Sambas Regency. Therefore, it is necessary to make efforts to study and preserve it. The aims of this research are (1) to describe the vocal melody of accompaniment music and (2) to describe the meaning of the verses in Raddat Ape Nang Ditumbok in Trimandayan Village, Teluk Keramat District, Sambas Regency. The research method used is descriptive with a qualitative form and a musicological and semantic approach. The data collection techniques used were observation and interviews, while the data collection tools used were interview guides, observation guidelines, research guidelines, digital cameras or smartphones, and notebooks. The validity of the data was tested using the source triangulation technique. The findings showed that the scales used in vocal melody dance accompaniment are major diatonic scales, with Andante tempo between 80-108 BPM. The bar used is 4/4 and has a 4- part song form. In the melodic motif, there is literal repetition, enlargement and reduction of intervals, and enlargement and reduction of tone values. In Ape Nang Ditumbok's Raddat vocal melody, there are no sequences and inversions. Raddat Ape Nang Ditumbok briefly delivers a moral message to the younger generation to uphold the rules, customs, manners in life, be grateful for the gift of life, work together, and help each other in society.Keywords: Analysis, Melody, Raddat Ape nang ditumbok, Sambas Regency.